AB0628 ANALYSIS OF CLINICAL FEATURES OF 15 CASES OF IGG4-RELATED DISEASES. (June 2019) - Yang, Ge; Su, Yazhen; Zhang, Gailian; Zhang, Liyun; Xu, Ke
Abstract : Background: IgG4-related disease is an autoimmune disease of unknown cause. Objectives: Summarizing the clinical characteristics of IgG4-related diseases to improve the understanding of clinicians and achieve early diagnosis and reasonable treatment. Methods: The clinical data of 15 patients with IgG4-related diseases diagnosed in our hospital from 2014 to 2018 were retrospectively analyzed. Results: The ratio of male to female was 2:1 in 15 patients. The average age of onset was 56.8 years (34 to 84 years of age). From the first symptom to the diagnosis of 8 days to 4.75 years, the most common first symptom in 15 patients was Submandibular gland swelling, pain, anorexia, cough, the most common affected organs are the pancreas, lungs, submandibular glands. There were 11 cases of histopathological examination by surgery or needle biopsy. The histopathology showed interstitial fibrous tissue hyperplasia with more lymphocyte and plasma cell infiltration. Immunohistochemistry showed that the number of IgG4-positive cells was >50/HPF, and IgG4/IgG was >40%.Two of the 15 patients underwent surgical resection of the affected organ occupying lesions before definitive diagnosis. One patient was treated with mycophenolate mofetil and one patient was given a medium dose of hormone combined with tamoxifen. The remaining 13 patients were treated with simple hormones or combination immunosuppressive agents, including hydroxychloroquine, mycophenolate mofetil, azathioprine, and cyclophosphamide. Conclusion: The organs involved in IgG4-related diseases are diverse, the clinical manifestations are not specific, and the hormone combined immunosuppressive therapy is effective. References: [1] Umehara H, Okazaki K, Masaki Y, et al. Comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD), 2011[J]. Japanese Journal of Rheumatology, 2012, 22(1):21-30. [2] Okazaki K, Kawa S, Kamisawa T, et al. Japanese clinical guidelines for autoimmune pancreatitis[J]. Pancreas, 2009, 38(8):849-866. Disclosure of interests: None declared